IMPLIKASI POLITIK PENEGAKAN HUKUM PIDANA DALAM UNDANG-UNDANG NOMOR 32 TAHUN 2009TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP TERHADAP UPAYA PENEGAKAN HUKUM LINGKUNGAN HIDUP - David Aprizon Putra (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2018)
Abstract: Since 1982 in Law Number 4 of 1982 concerning Environmental Management Principles which was later amended in 1997 to become Law Number 27 of 1997 concerning Environmental Management, legal politics regarding criminal law policy has been carried out. Law Number 32 of 2009 concerning Protection and Management of the Environment (UUPPLH) as the latest generation, has included criminal provisions in Chapter XV, which consists of 23 articles. The results of the study show that criminal law enforcement against formal offenses has a special procedural law, because it relates to the principle of ultimum remedium, meaning that the use of criminal law against formal offenses must wait until administrative law enforcement is declared ineffective. In order to avoid difficulties in enforcing environmental law that is sometimes used by certain elites to seek profits by looking at the gap in the weak regulations in the laws and regulations, the legislation, especially regarding formal law, must be clearly arranged, firm, not multiple interpretations.Keywords: Politic Criminal Law Enforcement, Environmental Law Enforcement